2007
DOI: 10.1007/s11517-007-0196-8
|View full text |Cite
|
Sign up to set email alerts
|

On the radiobiological impact of metal artifacts in head-and-neck IMRT in terms of tumor control probability (TCP) and normal tissue complication probability (NTCP)

Abstract: To investigate the effects of distorted head-and-neck (H&N) intensity-modulated radiation therapy (IMRT) dose distributions (hot and cold spots) on normal tissue complication probability (NTCP) and tumor control probability (TCP) due to dental-metal artifacts. Five patients' IMRT treatment plans have been analyzed, employing five different planning image data-sets: (a) uncorrected (UC); (b) homogeneous uncorrected (HUC); (c) sinogram completion corrected (SCC); (d) minimum-value-corrected (MVC); and (e) streak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Our study thus suggests that override of different structures by a single HU value can introduce errors on the order of 3 mm for (worst case) proton dose planning. These are of the same order of magnitude as the errors from metal artifacts reported in the literature …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our study thus suggests that override of different structures by a single HU value can introduce errors on the order of 3 mm for (worst case) proton dose planning. These are of the same order of magnitude as the errors from metal artifacts reported in the literature …”
Section: Discussionsupporting
confidence: 72%
“…Errors in these estimates directly translate to errors in, for example, the calculated water equivalent thickness (WET) and particle range. The CT additionally provides image material for organ and lesion delineation, whose accuracy could be reduced by the artifacts …”
Section: Introduction and Purposementioning
confidence: 99%
“…In a subsequent study, they also demonstrated that the tumor control probability (TCP) decreases as well as normal tissues complication probability (NTCP) increases in regions where metal artifacts have a relevant impact on image quality. 10 Balazova et al 9 found errors up to 25% in a phantom filled with steel inserts and irradiated with 6 MV photon beam and 20% dose discrepancies in a prostate patient treated with 18 MV. Moreover, a phantom study in 2007 (Ref.…”
Section: Introductionmentioning
confidence: 79%
“…Other authors have addressed this topic, pointing out the importance of MAR algorithm for accurate photon dosimetry. [4][5][6][7][8][9][10] However, no investigation on the effect of different metal materials with respect to image quality and dose calculation accuracy was performed. Our hypothesis was that, due to the chemical and physical characteristics of metals, such as atomic number, atomic mass, and mass density, the interaction of photon beams with implants differs thus significantly affecting the magnitude of (1) CT image artifacts and (2) dose inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation